Pengaruh Penerapan Model Pembelajaran Scaffolding terhadap Hasil Belajar Matematika pada Siswa Kelas VIII Semester Ganjil SMP Negeri 30 Bandar Lampung - Rahmawati, Fitriana (Lentera: Jurnal Ilmiah Kependidikan, 2016)
This study aims to determine whether there is an influence of scaffolding learning model application towards the learning outcomes of Mathematics in the first semester of eighth grade students of SMP Negeri 30 Bandar Lampung. This research used quantitative descriptive method, analysis of data using statistical formulas. The population in this study was all students of eighth grade students of SMP Negeri 30 Bandar Lampung consisting of five classes with the number of 156 students, while samples were taken two classes of class VIII B as the experimental class and class VIII E as the control class. To be able to know the results of student learning researchers conducted tests in the form of essays. Hypothesis testing used t-test statistical formulas.